2017
DOI: 10.1111/aos.13369
|View full text |Cite
|
Sign up to set email alerts
|

Visual function response to ocriplasmin for the treatment of vitreomacular traction and macular hole

Abstract: PurposeTo assess the effect of an intravitreal ocriplasmin injection on visual function, measured using visual acuity (VA) and vision‐related quality of life.Methods Post hoc analysis of prespecified secondary end‐points in two multicentre, randomized, double‐masked, phase 3 clinical trials. A total of 652 participants with symptomatic vitreomacular adhesion were enrolled, of whom 464 received a single intravitreal injection of 125 μg ocriplasmin and 188 received a single intravitreal placebo injection. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Macular hole (MH) surgery currently consists of pars plana vitrectomy (PPV), internal limiting membrane (ILM) peeling and gas tamponade (Kelly & Wendel 1991;Wendel et al 1993;Ko et al 2017;Hamoudi et al 2018). It has also been shown that MHs can be successfully treated with intravitreal ocriplasmin in cases of MHs associated with vitreomacular adhesion and vitreomacular traction (Jackson et al 2017). The success rate of MH closure with these procedures has improved to at least 90%.…”
Section: Introductionmentioning
confidence: 99%
“…Macular hole (MH) surgery currently consists of pars plana vitrectomy (PPV), internal limiting membrane (ILM) peeling and gas tamponade (Kelly & Wendel 1991;Wendel et al 1993;Ko et al 2017;Hamoudi et al 2018). It has also been shown that MHs can be successfully treated with intravitreal ocriplasmin in cases of MHs associated with vitreomacular adhesion and vitreomacular traction (Jackson et al 2017). The success rate of MH closure with these procedures has improved to at least 90%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all results were reported irrespective of vitrectomy, meaning if a patient’s eye disease deteriorated and required a vitrectomy this was not considered as a treatment failure (or nonresponse). The two reports by Jackson et al26 and Lescrauwaet et al30 also reported secondary outcomes from the same RCTs, however, a patient-centered composite endpoint consisting of visual acuity, VFQ-25 and need for vitrectomy was reported. In these responder analyses, a patient was considered a visual function responder when a clinically meaningful improvement in any of these principal traits of visual functioning was achieved, without the need for a vitrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 presents the study flow diagram with numbers of records screened, assessed for eligibility and included in the review. A total of six publications were included in this review: two reports of three RCTs: Stalmans et al,11 Dugel et al;12 and four reports that analyzed PRO outcomes from the same RCT: Gandorfer et al,23 Varma et al,29 Jackson et al,26 Lescrauwaet et al30…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations